Characterization of experimental cattle populations from Argentina with a low-density SNP genotyping panel - Michiels, Brian; Pardo, Alan Maxs; Ortega Masague, Maria Florencia; Giovambattista, Guillermo; Corva, Pablo (Wiley, 2022)
The objectives of the present experiment were to evaluate a low-density SNP array designed for the molecular characterisation of gene banks and to assess the genetic diversity and population structure of beef cattle herds from an Argentinean research station. Forty-nine animals from three breeds (Angus, Hereford, and Argentinean Creole) were genotyped using the multi-species IMAGE001 60-K SNP array (10 K for cattle). Genotypes of other 19 cattle populations from Argentina, other American countries, and Europe were included in the study. Of special interest was the characterization of the Argentinean Creole, the only autochthonous cattle breed in the country. Due to the merging of different datasets, approximately 5 K SNPs were effectively used. Genetic differentiation (FST), principal component analysis, neighbour-joining tree of Reynolds distances and ancestry analysis showed that autochthonous American breeds are clearly differentiated, but all have genetic influences of Iberian cattle. The analysed herds of Argentinean Creole showed no evidence of recent admixture and represent a unique genetic pool within local American breeds. An experimental herd and the local commercial Hereford population have also diverged, probably due to the influence of current selection objectives in the breed. Our results illustrate the utility of using low-cost, low density SNP arrays in the evaluation of animal genetic resources. This type of panels could become a very useful resource in developing countries, where most endangered cattle breeds are located. The results also reinforce the importance of experimental herds as reservoir of genetic diversity, particularly in the case of local breeds under-represented in traditional production systems.